Fringing field and short channel effects in thin-body SOI MOSFETs with shallow source/drain - Jui-Kai Hsia (IEEE Publishing, 2024)
This work explores numerically the short-channel effects in thin-body SOI MOSFETs with shallow source/drain architecture, where the junction depths are less than the associated silicon body thicknesses. Unique fringing field and short-channel behavior are observed in the unconventional SOI devices. Numerical results of the short-channel effects are compared with those in the conventional SOI MOSFETs. For given silicon body thicknesses, the shallow junction SOI devices exhibit the superior short-channel immunity over the conventional counterparts.